(untitled) (Cuea Journal of Business and Economics, 2025)
The cosmetic industry has historically targeted female consumers, yet in the last decade, urban male participation in grooming and personal care has grown significantly. Despite this trend, marketing strategies in Kenya remain largely female-oriented, creating a gap in addressing male consumer needs. This study examined the effect of search engine optimization (SEO) on the buying behaviour of urban male consumers in the cosmetic industry in Nairobi County, Kenya. The study adopted a quantitative approach and causal research design. A structured questionnaire with Likert-scale items was administered to a sample of 139 male consumers, selected through simple random sampling from a target population of 214. Data analysis employed descriptive statistics, correlation, and multiple linear regression, with diagnostic tests confirming model validity. The findings established that search engine optimization had a positive and significant effect on consumer behaviour. The study also found that SEO improved brand visibility and trust, translating into higher purchase intent. It recommends that cosmetic brands invest in credible influencer partnerships, create personalized and interactive social media campaigns, and strengthen content strategies to build long-term trust. Policy makers and industry stakeholders should also promote gender-inclusive marketing approaches to maximize market potential.